(untitled) (Texas Journal of Engineering and Technology, 2022)
This In recent decades, many researchers proposed fuzzy Sliding Mode Control (SMC) strategies that aim to eliminate the chattering problem in control of Multi-Input-Multi-Output (MIMO) nonlinear robotics manipulator systems. All these methods impose the need to determine the dynamic model of system under control, which is a challenging task in many practical cases. This paper presents a new model free and chattering free SMC method for MIMO nonlinear robotics manipulator systems based on Proportional-Derivative (PD) and fuzzy logic control. Proposed controller combines the robustness feature of SMC, simplicity of Proportional-Integral-Derivative (PID) control and ability of fuzzy technique in function approximation of discontinuity part of traditional SMC. In this paper, PD control is used as equivalent control in order to stabilize the system while adaptive fuzzy SMC is used to handle uncertainty of the system. Lyapunov’s second method is utilised to prove stability of proposed controller. Two different robotic manipulator configurations; two-links with payload and three links robotic manipulator under external disturbance and system uncertainties are simulated to demonstrate the efficiency of the proposed method.